2021
DOI: 10.3390/cryst11091085
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of ortho-t-BuSO2C6H4-Substituted Iodonium Ylides

Abstract: Iodonium ylides have recently attracted much attention on account of their synthetic applications. However, only a limited number of reports concerning the properties and reactivity of iodonium ylides exist, which is partly due to their instability. In this study, we synthesized several iodonium ylides that bear both an electron-withdrawing group and an aromatic ring with an ortho-t-BuSO2 group. Based on the crystal structures of the synthesized iodonium ylides in combination with natural-bond-orbital (NBO) ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The reaction pathways followed by iodonium ylides and Lewis basic reaction partners, from the initial adducts they form to the different products they produce, has long been a cause for discussion. This concept was elegantly illustrated by Kobayashi and Takemoto ( Scheme 1 ) [ 101 ], who suggested that an ylide 1 may halogen bond with a nucleophile using either of its σ-holes to generate intermediates 2 or 3 , where the cis -oriented ligands may reductively eliminate to generate either a functionalized β-dicarbonyl ( 4 , most common) or a substituted arene ( 5 , rare). Interestingly, when the first iodonium ylide was synthesized by Neiland and co-workers in 1957, they also evaluated its decomposition [ 1 , 102 ].…”
Section: Reviewmentioning
confidence: 99%
“…The reaction pathways followed by iodonium ylides and Lewis basic reaction partners, from the initial adducts they form to the different products they produce, has long been a cause for discussion. This concept was elegantly illustrated by Kobayashi and Takemoto ( Scheme 1 ) [ 101 ], who suggested that an ylide 1 may halogen bond with a nucleophile using either of its σ-holes to generate intermediates 2 or 3 , where the cis -oriented ligands may reductively eliminate to generate either a functionalized β-dicarbonyl ( 4 , most common) or a substituted arene ( 5 , rare). Interestingly, when the first iodonium ylide was synthesized by Neiland and co-workers in 1957, they also evaluated its decomposition [ 1 , 102 ].…”
Section: Reviewmentioning
confidence: 99%
“…Y. Takemoto, Y. Kobayashi and co-authors report the successful synthesis of orthot BuSO 2 C 6 H 4 -substituted iodonium ylides (which are known for their variety of synthetic applications) [7]. This research group estimate the strength of the intra-and intermolecular halogen-bonding interactions in the ylides salts and investigate their photoreactions.…”
mentioning
confidence: 99%
“…14 We chose ortho-SO 2 -t-Bu-substituted iodobenzene diacetate 13a,b (1) for its expected reactivity as well as the potential solubility and stability of the corresponding products. 16 The treatment of trifluoroacetamide (3a) and 1 with sodium hydride in dichloromethane at −20 °C successfully afforded N-trifluoroacetylated iminoiodane 5a in a 72% yield (entry 1). However, the use of pentafluoro-npropanaminde (3b) and heptafluoro-n-butanamide (3c) resulted in decreased yields (entries 2 and 3, respectively), presumably due to the poorer nucleophilicities of the perfluorinated amides.…”
mentioning
confidence: 99%
“…We began by preparing a series of N -perfluoroacylated iminoiodanes according to a reported procedure that used an iodoarene diacetate and a perfluorinated amide under basic conditions (conditions A, Table ). We chose ortho -SO 2 - t -Bu-substituted iodobenzene diacetate , ( 1 ) for its expected reactivity as well as the potential solubility and stability of the corresponding products . The treatment of trifluoroacetamide ( 3a ) and 1 with sodium hydride in dichloromethane at −20 °C successfully afforded N -trifluoroacetylated iminoiodane 5a in a 72% yield (entry 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation